The Correlation of Size of Core Network and Frequency of Contacts with Agitation and Positive Affect in Elderly with Dementia - (:unkn) unknown (My University, 2017)
In the country of Oman, care needs of older adults are primarily provided by family members in the home. The study was guided by socioemotional selectivity theory, the environmental vulnerability hypothesis, and the need-driven dementia-compromised behavior theories. The central premise was that the size of the person’s activities of daily living (ADL) core network and frequency of contact with the ADL core network would predict agitation and affect. A smaller core network with a higher frequency of contact may be better at identifying and treating the person’s unmet needs. A secondary premise was that the emotional closeness of the core network to the care recipient would predict the density of the ADL and instrumental activities of daily living (IADL) care provided. The purpose was to examine the associations between size and frequency of contact with the care providing core network and agitation and affect of PWD. The convenience sample of 98 PWD living in their homes was obtained from the Al Batinah South region in Oman. Participants’ were mostly female (63.3%) with a mean age of 80 years. Seventy-seven participants were classified with severe dementia and 21 had mild to moderate levels of dementia. Variables were measured through report from caregivers and the PWD using valid and reliable instruments. Unlike what was hypothesized, results did not show a significant association between size of and frequency of contact with ADL and IADL core networks and agitation and affect. Also, results did not show a significant association between closeness of IADL and ADL caregivers or the size of core networks to the density of IADL and ADL care provided. Caregivers continued to care and have the same frequency of contact throughout the progress of dementia. Findings are inconsistent with Western studies showing older adults prefer a smaller, closer social network that provides them with meaningful interactions. Differences in findings may be explained by the strong Omani cultural value to personally care for older parents. Understanding these relationships is critically important to designing interventions in Oman for home health care.
Keywords: Adl and Iadl; Affect; Agitation; Dementia; Frequency of Contact; Size of Core Network